A development of fractal PIFA (Planar Inverted F Antenna) with bandwidth enhancement for mobile phone applications - Saidatul Norlyana, Azemi; Azremi, Abdullah Al Hadi; R. Badlishah, Ahmad, Prof. Madya Dr.; Soh, Ping Jack; Malek, Fareq, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/